2023
DOI: 10.1136/bmjopen-2022-070720
|View full text |Cite
|
Sign up to set email alerts
|

Rationale and Design of the Rivaroxaban Post-Transradial Access for the Prevention of Radial Artery Occlusion Trial (CAPITAL-RAPTOR)

Abstract: IntroductionTransradial access (TRA) has rapidly emerged as the preferred vascular access site for coronary angiography and percutaneous coronary intervention. Radial artery occlusion (RAO) remains as an important complication of TRA as it precludes future ipsilateral transradial procedures. While intraprocedural anticoagulation has been studied extensively, the definitive role of postprocedural anticoagulation has not yet been established.Methods and analysisThe Rivaroxaban Post-Transradial Access for the Pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…Specifically, studies in rodents have suggested that DOACs exert pleiotropic effects on ECs through PAR mediation confirming their existence ( Lee et al, 2012 ; Pingel et al, 2014 ; Villari et al, 2017 ; Rahadian et al, 2020 ; Ito et al, 2021 ). Furthermore, ongoing investigations in clinical settings ( Di Santo et al, 2023 ) have shed additional light on the pleiotropic effects of DOACs, and evidence has already emerged from clinical studies, indicating that DOACs improve cardiovascular health beyond their primary anticoagulant function ( Pistrosch et al, 2021 ; Lin et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, studies in rodents have suggested that DOACs exert pleiotropic effects on ECs through PAR mediation confirming their existence ( Lee et al, 2012 ; Pingel et al, 2014 ; Villari et al, 2017 ; Rahadian et al, 2020 ; Ito et al, 2021 ). Furthermore, ongoing investigations in clinical settings ( Di Santo et al, 2023 ) have shed additional light on the pleiotropic effects of DOACs, and evidence has already emerged from clinical studies, indicating that DOACs improve cardiovascular health beyond their primary anticoagulant function ( Pistrosch et al, 2021 ; Lin et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%